ANALISIS PEMANFAATAN MEDIA PEMBELAJARAN AUDIO-VISUAL PADA MATA KULIAH BILINGUAL PROFESI KEPENDIDIKAN - Vidya Dwi Amalia Zati; Jubaidah Jubaidah; Sani Susanti; Raras Firdarianti (Universitas Negeri Medan, 2021)
Abstract: The Bilingual Educational Profession course is one of the Basic Educational Courses given to students in several study programs in the Bilingual FMIPA study program which in the learning process uses two languages, namely Bahasa Indonesia and English. One of the learning media that can be used in bilingual learning in the Educational Profession course is audio-visual learning media where this learning media combines sound and image elements that can provide an interesting learning experience for students, because learning by using this media will involve various senses, namely sight and hearing sense, so it will be able to train the sensory abilities needed for cognitive development. The purpose of this study is to find out 1) the use of audio-visual learning media to help students understand the material in the Bilingual Educational Profession course, 2) the use of audio-visual learning media to increase student concentration in the Bilingual Educational Profession course and 3) the description ofstudents’ feelings when using audio-visual learning media in the Bilingual Educational Profession course. This research uses qualitative research. The source of data or participants in this study were students of the Bilingual Natural Science Education study program in the 2020/2021 academic year. Data was collected through interviews, observations and documentation, so that the data obtained were the results of interviews in the form of responses, criticisms and suggestions from the participants. Data analysis techniques used include data reduction, data presentation and drawing conclusions. The results showed that: 1) Audio-visual learning media was effective in helping students to understand the materials in the Bilingual Educational Profession course, 2) The use of audio-visual learning media could increase student concentration in the Bilingual Educational Profession course, and 3) The use of audio-visual learning media in the Bilingual Educational Profession course can evoke a variety of positive feelings and emotions in students, including feeling comfortable, happy, motivated, not bored, relaxed and so on.Keywords: Bilingual, Audio Visual Learning Media, Educational ProfessionAbstrak: Mata kuliah bilingual Profesi Kependidikan adalah salah satu Mata Kuliah Dasar Kependidikan yang diberikan kepada mahasiswa pada beberapa prodi di prodi Bilingual FMIPA yang dalam proses pembelajarannya menggunakan dua Bahasa, yakni Bahasa Indonesia dan Bahasa Inggris. Salah satu media pembelajaran yang dapat dimanfaatkan dalam pembelajaran mata kuliah bilingual Profesi Kependidikan adalah media pembelajaran audio-visual dimana media pembelajaran ini menggabungkan unsur suara dan gambar yang dapat memberikan pengalaman belajar yang menarik bagi mahasiswa, dikarenakan pembelajaran dengan menggunakan media ini akan melibatkan berbagai indera, yakni indera penglihatan dan pendengaran, sehingga dapat melatih kemampuan sensorik yang diperlukan untuk perkembangan kognitif.Adapun tujuan dari penelitian ini adalah untuk mengetahui 1) pemanfaatan media pembelajaran audio visual untuk membantu mahasiswa dalam memahami materi pada mata kuliah Bilingual Profesi Kependidikan, 2) pemanfaatan media pembelajaran audio visual untuk meningkatkan konsentrasi mahasiswa pada mata kuliah Bilingual Profesi Kependidikan dan 3) gambaran perasaan mahasiswa saat menggunakan media pembelajaran audio visual pada mata kuliah Bilingual Profesi Kependidikan.Penelitian ini menggunakan penelitian kualitatif. Sumber data atau partisipan dalam penelitian ini adalah mahasiswa prodiBilingual PendidikanIPA Dasar stambuk 2020 pada tahun ajaran 2020/2021.Pengumpulan data dilakukan melalui wawancara, observasi dan dokumentasi, sehingga data yang diperoleh adalah hasil wawancara berupa tanggapan, kritik dan saran dari partisipan. Teknik analisis data yang digunakan meliputi reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa:1) Media pembelajaran audio visual efektif dalam membantu mahasiswa dalam memahami materi pada mata kuliah Bilingual Profesi Kependidikan, 2)Pemanfaatan media pembelajaran audio visual dapat meningkatkan konsentrasi mahasiswa pada mata kuliah Bilingual Profesi Kependidikan, dan 3) Pemanfaatan media pembelajaran audio visual pada mata kuliah Bilingual Profesi Kependidikandapat membangkitkan berbagai perasaan dan emosi positif pada mahasiswa, antara lain perasaan nyaman, senang, termotivasi, tidak bosan, santai dan sebagainya.Kata Kunci: Bilingual, Media Pembelajaran Audio Visual, Profesi Kependidikan